Frequency-selective non-linear blending for the computed tomography diagnosis of acute gangrenous cholecystitis: Pilot retrospective evaluation. (2018) - Schwarz, R.; Bongers, N.M.; Hinterleitner, C.; Ditt, H.; Nikolaou, K.; Fritz, J.; Bösmüller, H.; Horger, M.
Abstract: Purpose: To compare the diagnostic performance of frequency-selective non-linear blending and conventional linear blending contrast-enhanced CT for the diagnosis of acute (AC) and gangrenous (GC) cholecystitis. Materials and methods: Following local ethics committee approval for retrospective data analysis, a database search derived 39 patients (26 men, mean age 67.8 ± 14.6 years) with clinical signs of acute cholecystitis, contrast enhanced CT (CECT) evaluation, cholecystectomy, and pathological examination of the resected specimen. The interval between CECT and surgery was 4.7 ± 4.1 days. Pathological gross examination was used to categorize the cases into AC and GC. Subsequently, two radiologists categorized the CECT studies in a blinded and independent fashion into AC and GC, during two different reading sessions using linear blending and frequency-selective non-linear blending CECT. Results: Histologic analysis diagnosed 31/39 (79.4%) cases of GC and 8/39 (20.6%) cases of AC. Image interpretation of linear blending CECT resulted in classification of 7/39 (17.9%) patients as GC and 32/39 (82.1%) as AC, whereas image interpretation of frequency-selective non-linear blending CECT resulted in classification of 29/39 (74.3%) patients as GC and 10/39 (25.7%) as AC. Sensitivity/specificity/PPV/NPV for detection of GC were 22.6%/100%/100%/25% with linear blending CECT and 80.6%/50%/86.2%/40% with frequency-selective non-linear blending CECT, respectively. Based on the histopathologic diagnosis frequency-selective non-linear blending had a significant improvement (p > 0.0001) in the diagnostic accuracy of gangrenous cholecystitis compared with linear blending. Conclusion: Frequency-selective non-linear blending post-processing increases the diagnostic accuracy of gangrenous cholecystitis owing to improved visualization of absence of focal enhancement and mural ulcerations.